Pengaruh Eco-Enzyme sebagai Nutrisi terhadap Pertumbuhan Tanaman Selada Hijau (Lactuca sativa) pada Metode Hidroponik Sistem Wick di Kota Samarinda - Sofian, Roza Adnan; Kurniawati, Zenia Lutfi; Turista, Dora Dayu Rahma; Purwati, Sri; Masitah, Masitah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Green lettuce (Lactuca sativa) is a horticultural crop that is becoming increasingly popular due to its high nutritional content. This plant plays an important role in improving the nutritional intake of the community. This study aimed to determine the effect of using eco-enzyme on the growth of green lettuce plants and to identify the best concentration. The research was conducted from June to August 2025 on a limited area using the wick hydroponic system located on Jalan Abdul Wahab Syahrani, Gang Wangi, Gunung Kelua, Air Hitam, Samarinda City, East Kalimantan Province. This study used a Randomized Block Design (RBD) consisting of five treatments, each repeated five times, namely: P0 (control/1 L), P+ (control plus/AB mix 10 ml/L), P1 (EE 10 ml/L), P2 (EE 15 ml/L), and P3 (EE 20 ml/L). Data on plant height and number of leaves were analyzed using Two-way Multivariate Analysis of Variance (Two-way MANOVA) followed by the Bonferroni test at a 5% significance level. Meanwhile, the data on fresh weight were analyzed using One-way Analysis of Variance (One-way ANOVA). The results showed that eco-enzyme treatment had a significant effect on plant height, number of leaves, and fresh weight of green lettuce, with the best concentration obtained from treatment P1 (EE 10 ml/L).